The Rock Where We Stand : An Ethnography of Women's Activism in Newfoundland - George, Glynis R. (Glynis Rosamonde), 1964- (Book collections on Project MUSE., 2000)
"This ethnography explores how women at the Bay St. George Women's Council deal specifically with the issues of poverty, single motherhood, child sexual abuse, and domestic violence, and examines the interplay of feminist and Newfoundland identification among these individuals." "Drawing on fourteen months of observation and interviews with women at the council, Glynis George provides a much needed, specifically Canadian, contribution to ethnocultural and feminist studies. The research situates the particular concerns and political activism of these women in this rural region of Canada within the larger context of economic restructuring and neo-liberal economic and social policies that continue to marginalize women in Canada and around the world."--Jacket.